Dysphagia in Alzheimer's disease - N. N. Koberskaya (Неврология, нейропсихиатрия, психосоматика, 2022)
The article highlights the problem of dysphagia, which is often present in patients with Alzheimer's disease (AD), as a rule, at advanced stages of the disease and significantly complicates the management of this group of patients. Issues of age-related physiologic swallowing changes are considered. Mechanisms of dysphagia development in the elderly and in AD patients are discussed. It is noted that in AD areas of the cerebral cortex, involved in the act of normal swallowing are affected. The most dangerous complication of dysphagia is aspiration, which increases the risk of pneumonia and death. It is noted that dysphagia in patients with AD leads to weight loss and increased dependence on nutrition. Weight loss increases the risk of opportunistic infections in patients with AD. In the case of dysphagia symptoms development, pill administration causes great problems. In this scenario, the solution is the use of dispersible or liquid forms of drugs. We describe a clinical case of severe AD in which a dispersible form of memantine, Memoritab, was used. The complications associated with dysphagia in patients with AD highlight the importance of early detection and treatment of this symptom. Understanding the specific pathological processes of the underlying disease that contribute to the development of dysphagia is necessary in order to adapt the treatment of patients in a timely fashion.